"Molière amoché": Discourse on the quality of English-speaking Canadian politicians' French in Canadian news media coverage of the 2020 conservative leadership debate. (May 2023) - Bosworth, Yulia
Abstract: "In the course of a federal electoral campaign in Canada, the French language ability of the candidates is widely discussed in both French-language and English-language media. This article proposes a discourse analysis of a representative sample of articles recovered in both French-language (20) and English-language (15) online news publications targeting the French language proficiency of candidates who have participated in the 2020 Conservative leadership French-language debate. Through an examination of representations of the French language and French language ability, the study develops a comparative analysis of the evaluation of French language ability of English-speaking Canadian politicians in the French-language and English-language Canadian media in a comparative perspective, demonstrating that the divergent language representations and the ideologies they underpin condition a number of differences between the two respective discourses: the overwhelmingly negatively constructed commentary in the French-language corpus, the construal of French language ability as an acquirable skill and a tool of communication by English Canadian journalists and as an intrinsic faculty by French Canadian journalists, and the positing of a monolingual educated native speaker as a standard in French Canadian journalistic metadiscourse on language, with no such standard discernible in the English Canadian discourse. Crucially, in examining the ways in which the two discourses interact, and, potentially, influence one another, the analysis shows the reproduction of discourse to be unidirectional, with French-language discourse influencing its English-language counterpart. This finding suggests an important role of language ideologies circulating in the French-language press in judging French language ability in Canada, which can be problematic for bilingual speakers and adult learners of French, such as English-speaking Canadian politicians." Highlights: Prominent focus on French language ability of English Canadian politicians preceding and following important events of the election cycle in both French Canadian and English Canadian press. Overwhelmingly negative construal of French language ability of English-speaking politicians by French Canadian journalists, underpinned by the ideologies of the standard, of monolingualism, and of bilingualism. Construal of French language ability as an acquirable skill and a tool of communication by English Canadian journalists – instrumental language ideologies. Monolingual educated native speaker as a standard in French Canadian journalistic metadiscourse, unstable standard in English Canadian discourse. Unidirectional influence of French Canadian discourse on its English Canadian counterpart, but not the reverse, problematic for English-Canadian politicians seeking to attain a positive evaluation of their French.